Real‐time quantitation of internal metabolic activity of three‐dimensional engineered tissues using an oxygen microelectrode and optical coherence tomography. Issue 4 (29th January 2016) - Kagawa, Yuki; Haraguchi, Yuji; Tsuneda, Satoshi; Shimizu, Tatsuya
Abstract: Recent progress in tissue engineering technology has enabled us to develop thick tissue constructs that can then be transplanted in regenerative therapies. In clinical situations, it is vital that the engineered tissues to be implanted are safe and functional before use. However, there is currently a limited number of studies on real‐time quality evaluation of thick living tissue constructs. Here we developed a system for quantifying the internal activities of engineered tissues, from which we can evaluate its quality in real‐time. The evaluation was achieved by measuring oxygen concentration profiles made along the vertical axis and the thickness of the tissues estimated from cross‐sectional images obtained noninvasively by an optical coherence tomography system. Using our novel system, we obtained (i) oxygen concentration just above the tissues, (ii) gradient of oxygen along vertical axis formed above the tissues within culture medium, and (iii) gradient of oxygen formed within the tissues in real‐time. Investigating whether these three parameters could be used to evaluate engineered tissues during culturing, we found that only the third parameter was a good candidate. This implies that the activity of living engineered tissues can be monitored in real‐time by measuring the oxygen gradient within the tissues. The proposed measuring strategy can be applied to developing more efficient culturing methods to support the fabrication of engineered thick tissues, as well as providing methods to confirm the quality in real‐time. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 855–864, 2017.